STRATEGI BERTAHAN HIDUP PETANI PENYADAP KARET DI DESA PULAU BIRANDANG KECAMATAN KAMPAR TIMUR KABUPATEN KAMPAR - Pertiwi, Kartini Putri; ", Nurhamlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
One of the available natural resources in Indonesia is a rubber plantation. In Riau Province,Kampar is the largest rubber producer with production in 2012 is 61.482 tonnes and 50.643families of farmers. As is the case in the village of Island Birandang the majority of thepopulation to 80% eyed quest as rubber farmers. Island residents Birandang his dependenceon rubber plantations. The problems discussed in this thesis is how the welfare and survivalstrategies of farmers in rubber tappers Birandang Island Eastern District of Kampar.Various ways or strategies do survive to be able to maintain its survival. As for the dataobtained in this study will use descriptive quantitative method. Techniques used indetermining the sample is simple random sampling, while the process of collecting data usinginterviews and observation.Results of studies conducted in general the writer can say that thewelfare of farmers in general are rubber tappers in the family entitled to the still relativelypoor, efforts should be made by farmers tapper that meet social needs that level ofpsychological well-being increased. Because of economic problems is a problemthatconcerns the welfare and subsistence people,then the survival strategies they are doing isthemost effective active strategy and networking strategy.Keywords: RubberTappersFarmers, Welfare, SurvivalStrategies